Axel Honneth and The Reconstruction of Justice: An Attempt to Overcome the "Distribution Paradigm" - Marques, Stanley Souza; de Oliveira, Marcelo Andrade Cattoni (Revista de Teorias da Justiça, da Decisão e da Argumentação Jurídica, 2015)
The article takes up the criticisms directed by Axel Honneth to the basic structure of the dominant conceptions of justice, but merely to point out the general outlines of his alternative project of justice normative reconstruction. If John Rawls and Michael Walzer structure theories of distributive justice very consistently and in order to get to the autonomy protection (already taken so) in a more sophisticated way, that to be satisfied it transcends the (mere) obligation of not interfering in the realization of individual life projects, Honneth proposes the radicalization of justice's demands. It is because he pays his attention to the mutual expectation of consideration. This point would be the new texture of the social justice. In this sense, the principles of fair distribution leave the scene to make way for principles which guidelines are directed towards the society basic institutions involved in a new goal: to set up favourable contexts for the success of plural reciprocal relationships.